2017
DOI: 10.1016/j.bbrc.2017.07.165
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics of the cryo-EM CFTR structure

Abstract: Cystic fibrosis (CF), a lethal monogenic disease, is caused by mutant variants of the CF transmembrane conductance regulator (CFTR). Recent advances in single molecule cryo-EM methods enabled structural determination of full-length human and zebrafish CFTR, achieving an important milestone for CF drug development. To relate these structures to the gating cycle, we examined its dynamic features using molecular dynamics simulations. Our results show that the nucleotide binding domains (NBDs) in this bottom-open … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 42 publications
2
11
0
Order By: Relevance
“…To overcome the limitations of static structures, several molecular dynamics studies have been performed. Tordai et al performed simulations with the apo zebrafish CFTR structure, which was determined in the absence of ATP and exhibited separated NBDs [21]. In this study, it was suggested that this conformation is not highly populated under physiological condition, since closure of the NBDs could be observed even in short simulations.…”
mentioning
confidence: 76%
“…To overcome the limitations of static structures, several molecular dynamics studies have been performed. Tordai et al performed simulations with the apo zebrafish CFTR structure, which was determined in the absence of ATP and exhibited separated NBDs [21]. In this study, it was suggested that this conformation is not highly populated under physiological condition, since closure of the NBDs could be observed even in short simulations.…”
mentioning
confidence: 76%
“…We have recently investigated the dynamics of the inward-facing CFTR cryo-EM structure and noticed the closure of the nucleotide binding domains ( Fig. 3 a in [ 44 ]). As the measures we have calculated were not sufficient to fully understand the movements of the protein in detail, we analyzed the trajectories employing conftors.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, at the intramolecular interaction site of the L0/Lasso motive preceding the first transmembrane domain in ABCC proteins, such as ABCC1/MRP1 (Fig. S7) and ABCC7/CFTR [ 44 ] the positive ring breaks with a hydrophobic spot. The functionally important amphipathic α-helix of the L0/Lasso motif binds to this patch as observed in several cryo-EM structures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, ideally, a resolution of 3 Å or better is necessary for structure based predictions and drug design. Structures at lower resolution can still be useful; molecular dynamics and other computational methods can be used to fit and minimize the structure and assign the most probable loop conformations and residue rotamers (Trabuco et al, 2008) (Zhao et al, 2013) (Arenz et al, 2016) (Tordai et al, 2017), as well as build de novo structures (Das and Baker, 2008) or identify the position of chemically relevant waters (Wang et al, 2011) (Jukič et al, 2017). The combination of low resolution experimental structures and modeling can become a powerful tool for SBDD, particularly if orthogonal validation methods and checks are available.…”
Section: Introductionmentioning
confidence: 99%